Implementation of perioperative breathing exercises and its effect on postoperative pulmonary complications and long-term prognosis in elderly patients undergoing laparoscopic colorectal surgery: A randomized controlled trial. (September 2022) - Chen, Jing; Peng, Li-Hua; Min, Su
Objective: This study was to investigate the impact of breathing exercises on recovery in elderly patients receiving laparoscopic colorectal surgery. Design: A prospective randomized controlled trial. Setting: University hospital. Subject: A total of 264 elder patients undergoing laparoscopic colorectal surgery participated in this study. Intervention: Patients in intervention group received respiratory-related exercises based on standardized enhanced recovery after surgery strategies from admission to 90 days after surgery. The control group received perioperative standardized enhanced recovery after surgery strategies without formatted breathing exercises. Main measures: The primary outcome was the incidence of postoperative pulmonary complications. The secondary outcomes included 6-minute walking distance, surgery-related complications, length of stay, mortality postoperatively, and hospitalization costs. Results: Completion rate of breathing exercise in intervention group was over 80% till 90 days postoperatively. The incidence of postoperative pulmonary complications was lower in breathing exercises group (17/132 [12.9%] vs. 43/132 [32.6%], p  < 0.001). The mean value of 6-minute walking distance increased more in intervention group compared with baseline values preoperatively (44.2 ± 4.3 vs. 3.2 ± 0.2, p  < 0.001). On 90 days postoperatively, the mean value of 6-minute walking distance in breathing exercises group increased by 18.8 m compared with its baseline (557.0 ± 133.5 vs. 538.2 ± 112.7, p  = 0.022), while that of control group decreased by 53.2 m from baseline (481.9 ± 102.5 vs. 535.1 ± 123.4, p  < 0.001). Patients who received breathing exercises had shorter length of stay and lower hospitalization costs ( p  < 0.050). Conclusions: Perioperative breathing exercises helped prevent postoperative pulmonary complications and improve long-term prognosis in elderly patients undergoing laparoscopic colorectal surgery.